Reconstruction of the Catalytic Pocket and Enzyme–Substrate Interactions To Enhance the Catalytic Efficiency of a Short‐Chain Dehydrogenase/Reductase. Issue 20 (13th September 2016) - Li, Aipeng; Ye, Lidan; Yang, Xiaohong; Wang, Bei; Yang, Chengcheng; Gu, Jiali; Yu, Hongwei
Abstract: To upgrade the short‐chain dehydrogenase/reductase EbSDR8 to a powerful tool for the synthesis of anti Prelog chiral alcohols, rational design was performed by reconstructing the catalytic pocket and enzyme–substrate interactions. The resulting variants showed significantly improved catalytic efficiency ( k cat / K M ; k cat =turnover rate, K M= Michaelis constant) towards a series of prochiral ketones, with k cat / K M values more than 15‐fold greater than that of wildtype EbSDR8 in some cases. More importantly, none of the mutations caused an adverse effect on the stereoselectivity. The increased steric repulsion and the C−H⋅⋅⋅ π interaction involving the alkyl side chain of L153 and the phenyl ring of the substrate turned out to be crucial factors connected to the enhanced enzymatic activity. This provided new insight into the role of steric hindrance and non canonical interactions in protein engineering. Furthermore, the recombinant E. coli whole cells expressing the EbSDR8 variant G94A/S153L successfully catalyzed the reduction of a high‐concentration 2, 2, 2‐trifluoroacetophenone. The results demonstrated the effectiveness of rational design and the applicability of the designed variants in the efficient reduction of prochiral ketones. Abstract : Reconstructing enzymes : The catalytic efficiency of the short‐chain dehydrogenase/reductase EbSDR8 is significantly improved by reconstructing the catalytic pocket and enzyme–substrate interactions. The resulting variants show significantly improved catalytic efficiencies towards the reduction of a series of prochiral ketones; in some cases, the efficiency is more than 15‐fold greater than that of wildtype EbSDR8.